Impacts of blood flow restriction training on lower limb strength qualities in elite university football players - Sun, Z.; Hu, C.; Zhang, X.; Liu, Y. (Sport Sciences for Health, 2025)
Purpose The primary aim of this study was to directly compare the effects of low-load (30% 1RM) blood flow restriction training (BFR), moderate-load (50% 1RM) BFR, and traditional high-load resistance training (70% 1RM) on improvements in maximal lower limb strength, rapid strength, and strength endurance in collegiate elite football players. We hypothesized that: under 50% limb occlusion pressure (LOP), blood flow restriction (BFR) training at 30% 1RM and 50% 1RM intensities elicits significantly differential effects on maximal strength, rapid force production, and strength endurance compared to traditional high-intensity resistance training (70% 1RM) in university elite football athletes.